Problems of thermonuclease detection for identifying Staphylococcus aureus in blood culture broths. Issue 9 (September 1991) - Megson, G M; Law, D; Ganguli, L A
Abstract : The detection of thermonuclease by the Oxford strain and eight clinical isolates of Staphylococcus aureus in a variety of bacteriological broths with and without added blood was examined using a toluidine blue-DNA-agar plate method. In Isosensitest, brain-heart infusion, tryptic soy, nutrient and gas-liquid chromatography broths (all of which do not contain liquoid) thermonuclease detection was uncomplicated. In Bactec broths (containing liquoid) detectable thermonuclease activity was greatly reduced in the absence of blood. The addition of 10% blood to the Bactec broths restored the activity. Liquoid was shown to be responsible for the inhibition of thermonuclease activity, and its effect could be neutralised by the addition of blood, albumin, or haemoglobin. In specimens containing no blood, or insufficient blood to neutralise the liquoid in culture broths, more has to be added to prevent false negative reporting of S aureus. This can be done after growth at the time of thermonuclease testing. Clinical consequences of delayed identification of S aureus in routine blood cultures may be serious. The application of the thermonuclease test to blood culture broths is both fast and specific.